2014
DOI: 10.1155/2014/457063
|View full text |Cite
|
Sign up to set email alerts
|

Can Tumor Necrosis Factor-αand Interleukin-6 Be Used as Prognostic Markers of Infection following Ureteroscopic Lithotripsy?

Abstract: Introduction. Ureteroscopic lithotripsy (URS) although highly effective for the treatment of ureteral stones is associated with certain complications, the more common of which are postoperative fever and infection. In the present study we aimed to evaluate the levels of serum cytokines in patients undergoing ureteroscopic lithotripsy and investigate any possible correlation between levels of cytokines and infectious complications after URS. Materials and Methods. Thirty patients (19 males, 11 females), with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…This increase is twice as high as what has previously been found in studies of COX-2 using chronically obstructed human ureters and experimental ureteral obstruction in pigs. 8 , 11 Similar studies regarding TNF-α induction in the human ureter after instrumentation have not been published; however, our results are supported by the findings of Schwentner and colleagues, 12 who showed that TNF-α levels were significantly higher in children with vesicoureteral reflux than in age-matched autopsy controls, and by Bantis and colleagues, 29 who found doubling of serum values 1 hour after ureteroscopic lithotripsy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This increase is twice as high as what has previously been found in studies of COX-2 using chronically obstructed human ureters and experimental ureteral obstruction in pigs. 8 , 11 Similar studies regarding TNF-α induction in the human ureter after instrumentation have not been published; however, our results are supported by the findings of Schwentner and colleagues, 12 who showed that TNF-α levels were significantly higher in children with vesicoureteral reflux than in age-matched autopsy controls, and by Bantis and colleagues, 29 who found doubling of serum values 1 hour after ureteroscopic lithotripsy.…”
Section: Discussionsupporting
confidence: 88%
“…A few studies exist regarding the role and function of TNF-α in the human ureter. In a study of 30 patients, serum TNF-α levels were significantly increased after 1 and 48 hours following ureteroscopic lithotripsy, 29 and in another study it was found significantly more abundant in the ureter of children with vesicoureteral reflux than in healthy controls. 12 …”
Section: Discussionmentioning
confidence: 89%
“…TNF-α not only can inhibit proliferation to induce apoptosis of cervical cancer cells by regulating the downstream nuclear factor-κB, receptor activating protein kinase 3, epidermal growth factor receptor and other proteins, but also can induce the proliferation, migration and invasion of cancer cells. Therefore, assessing the association between TNF-α and proliferation and apoptosis of cervical cancer cells is of great significance ( 13 16 ). Although studies have confirmed that miRNAs serve an important role in the proliferation and apoptosis of cancer cells, the study of miRNA regulation of TNF-α is still relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…We have read with great interest the paper published in a recent issue of ISRN Urology by Bantis et al [ 1 ] entitled “can tumor necrosis factor- α and interleukin-6 be used as prognostic markers of infection following ureteroscopic lithotripsy?” in which they report preoperative and postoperative serum interleukin-6 (IL-6) and tumor necrosis factor- α (TNF- α ) levels in patients with urolithiasis. In their paper, authors report these inflammatory markers' level and speculate that high preoperative levels of serum TNF- α and IL-6 may indicate a predisposition for postoperative inflammation and infection.…”
mentioning
confidence: 99%